Condiciones turísticas de las ciudades de Trujillo y Chiclayo para el desarrollo del turismo deportivo. - Armas Aguilar, Arturo Alexander (2019)
This thesis report takes place in the cities of Trujillo and Chiclayo. In this context, the main_x000D_ objective is determine the tourist conditions of the cities of Trujillo and Chiclayo for the_x000D_ development of sports tourism. Nowadays the cities of Trujillo and Chiclayo are known for_x000D_ their cultural tourism, with this report we propose to study another type of tourism related_x000D_ with the sports activities, identifying their conditions in sports infrastructure, identifying_x000D_ their annual sports programs, as well identifying the tastes and preferences of tourists and_x000D_ finally characterizing the tourism product of both cities in a technical way; therefore the_x000D_ investigation determined that the tourist conditions are favorable for having optimal sports_x000D_ scenarios, which is considered by tourists as a primary cause that would generate boost of_x000D_ sports tourism activity, the variety of sporting events in its annual programs of the_x000D_ municipality also is considered by tourists as a cause that would generate more his visit to_x000D_ the cities investigated._x000D_ For this research, the ethnographic method and the analytic-synthetic method have been_x000D_ used, supported by the techniques of direct observation, interview, survey, and signing._x000D_ And with their respective instruments such as the field notebook, camera, questionnaire of_x000D_ directed survey, interview guides applied to the main authorities linked to the sport_x000D_ activity, the observation cards and the analysis sheets.